Mimicry of Patriarchal Culture in the Form of Verbal Violence Towards Women in Instagram - Ananda, Sabilla Tri; Nurbani (Talenta Publisher, 2025)
This study aims to analyze how mimicry of patriarchal culture occurs through verbal violence against women on Instagram. Using Roland Barthes' semiotic method by analyzing the comments column in the form of verbal violence in the Instagram account @anneofficial1990, the research found that based on observations on the comment texts, the normalization of violence against women is the impact that occurs as a result of the entertainment media's spotlight on the account owner's decision to remove her hijab. The conclusion of this research is that mimicry occurs in the form of imitation of patriarchal culture and is manifested in verbal violence committed by women against other women. Women who are dominated by male masculinity in the real world try to make themselves as subjects through the arena on Instagram social media by oppressing other women through the comment section on Instagram. The myth found in this study is the myth of patriarchal culture, one of which is the assessment of women from the way they dress.